2021
DOI: 10.1037/apl0000824
|View full text |Cite
|
Sign up to set email alerts
|

The regulating role of mindfulness in enacted workplace incivility: An experience sampling study.

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 102 publications
(243 reference statements)
2
45
0
Order By: Relevance
“…It has also been shown to offer advantages in contexts that make employees susceptible to burnout and emotional exhaustion such as public offices, schools, and nursing homes (Dierynck et al, 2017;Hu ¨lsheger et al, 2013;Meiklejohn et al, 2012;Shapiro et al, 2006). Mindfulness has also been found to be beneficial in situations that require high selfregulation and moral maturity (Hu ¨lsheger et al, 2020) and in contexts that are mentally fatiguing due to multi-tasking (Kudesia et al, 2020).…”
Section: Balance As Contextual Sensitivitymentioning
confidence: 99%
“…It has also been shown to offer advantages in contexts that make employees susceptible to burnout and emotional exhaustion such as public offices, schools, and nursing homes (Dierynck et al, 2017;Hu ¨lsheger et al, 2013;Meiklejohn et al, 2012;Shapiro et al, 2006). Mindfulness has also been found to be beneficial in situations that require high selfregulation and moral maturity (Hu ¨lsheger et al, 2020) and in contexts that are mentally fatiguing due to multi-tasking (Kudesia et al, 2020).…”
Section: Balance As Contextual Sensitivitymentioning
confidence: 99%
“…According to Liu et al, 32 workplace incivility is characterized by disrespecting others to lead to a sense of disconnection, a break in interpersonal relations, as well as an underdeveloped empathy. 33 Studies of workplace incivility have examined incidents involving individual workers, including checking email during meetings, sending text messages during meetings, and expressing disrespectful remarks. 34 Two factors explain why scholars are paying more attention to these once-disregarded isolated incidents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relationships are critical in a team setup. Mindfulness reduces hostile behaviors by reducing irritation and anger (hostile feelings), and lessens Machiavellian tendencies, counterproductive work behaviors [103], and workplace incivility behavior [104]. Moreover, team mindfulness has been identified as a brilliant tool to preserve organizations from team conflict transformation processes.…”
Section: Team Mindfulnessmentioning
confidence: 99%
“…The way employees spend their time after work hours could be an influential factor in their work performance. The scholarship has demonstrated that higher mindfulness is positively associated with psychological and physical well-being-related dimensions, such as coworkers' daily positive affect, psychological detachment after work, relaxation experiences, sleep quality, sleep duration [43,160,[180][181][182][183], happiness [123], enhanced relationship satisfaction, minimized work-family conflicts [31,184,185], work-life enrichment [130], quality of life [122], reduced enacted incivility [104], reduced incidence of bad moods, enhanced satisfaction at work and home, and minimized daytime sleepiness and insomnia symptoms [151].…”
Section: Mindfulness and Employees' Well-beingmentioning
confidence: 99%